International Financial Reporting Standards Applied in the Czech Republic - Honková Irena (My University, 2015)
This article provides an extensive analysis of application of International Financial Reporting Standards companies with publicly traded shares in the Czech Republic for 2013. At first the attention is paid to the basic requirements of International Accounting Standards (IAS) and International Financial Reporting Standards (IFRS) and to evaluation of proposed method. Then followed research results, based on an answer to the question of whether the companies are preparing their financial statements in accordance with IAS / IFRS, i.e. whether they serve plenty of mandatory information, and further whether individual companies act similarly. The object of the research consists in further observations regarding the implementation of the new IFRS 9 Financial Instruments, which is designed to replace IAS 39 Financial instruments: recognition and measurement. The level of the information presented was evaluated using a signed test. Using this statistical method we can conclude that companies submit their financial statements in accordance with IAS / IFRS. Using the Friedman test, it was found that the group of companies proceeds with the application of individual IAS / IFRS alike. Only two of seven respondents have already implemented IFRS9. Statistical analysis confirmed that companies reported, in their financial statements, all mandatory information that is relevant to stakeholders. On the other hand, there are also signs pointing to the contrary, but these are not statistically significant. This analysis was provided with detailed knowledge about this phenomenon.
Mezinárodní standardy finančního výkaznictví aplikované v České republice
Keywords: International Financial Reporting Standards, international Accounting Standards, IFRS, IAS; Mezinárodní standardy finančního výkaznictví, mezinárodní účetní standardy, IFRS, IAS